Study of the Causes of Soil Pollution with Heavy Metals - Jalout, Alaa Hussein Naji; Mozan, Radwan Jabbar Shajr; Mahdi, Mohammed Assi daham; Zahra Abd, Enas Hamed Abdel; Abd Aidan, Maryem Mohammed (American Journal of Biodiversity, 2024)
Soil pollution caused by heavy metals has received extensive attention due to its accelerating severity and potential threat to environmental and human health. Determining the primary sources and causes of heavy metal pollution in soil is urgent and plays an important role in assessing the eco-environmental and human health risk. Soil is the primary reserve and supplier of water and nutrients for crops and, thus, the most viable indication of stress induced by heavy metals in the environment. Heavy metal pollution in soil can not only reduce the quality and yield of agricultural products and threaten human health but also undermine ecosystem services. Thus, the research of heavy metal pollution in soil is not only economically meaningful but also important for the sustainable development of agriculture, environmental safety, the protection of public health, and ecosystem health. "soil pollution" refers to damages caused by mixing foreign substances with soils, which in turn cause physical, chemical, or biological changes to the soils and adversely affect normal physical, chemical, and biological activities. Although researchers have slightly different definitions of "organic pollution" and "soil pollution" in terms of specific vocabulary, the essence of both definitions is the same. "soil pollution" as losses caused by human activities that deteriorate, degrade, destroy, and lead to the unavailability of the lands, and in which the agricultural production of these lands is affected to an extent. "soil pollution" as the presence in or on the soil of chemical substances in quantities that exceed natural background levels and thus may have direct or indirect adverse effects on humans and other biological species.